1991
DOI: 10.1159/000310233
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Amblyopia on High-Pass Resolution Perimetry

Abstract: Seventeen subjects with amblyopia due to strabismus and anisometropia were examined using high-pass resolution perimetry. In addition to the standard technique, testing the 5–30° visual field, an optional program testing the central 4° visual field was used. Threshold elevation was confined to the central 4° visual field and strongly correlated with visual acuity, expressed as minimum angle of resolution. Standard high-pass resolution perimetry did not reveal any significant abnormalities in the amblyopic subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…6 Stability of fixation has been shown to be abnormal in amblyopia. 8,22 In addition, in many studies 2,6,8,23,24 authors have identified central depressions in amblyopic patients, especially in those presenting with severe amblyopia and deprivation amblyopia. Johnson 8 reported that amblyopia is associated with a generalized depression of light sensitivity (greatest at the fovea and correlated with visual acuity loss) and small focal deficits.…”
Section: Discussionmentioning
confidence: 99%
“…6 Stability of fixation has been shown to be abnormal in amblyopia. 8,22 In addition, in many studies 2,6,8,23,24 authors have identified central depressions in amblyopic patients, especially in those presenting with severe amblyopia and deprivation amblyopia. Johnson 8 reported that amblyopia is associated with a generalized depression of light sensitivity (greatest at the fovea and correlated with visual acuity loss) and small focal deficits.…”
Section: Discussionmentioning
confidence: 99%